Validasi Modul CARE dalam Meningkatkan Kecerdasan Emosional Guru Sekolah Dasar Inklusi - Puti Ayu Setiani; Budi Andayani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
Teacher’s social-emotional competence has a significant role in effective teaching. The many challenges faced by teachers such as student’s negligent, student’s misbehavior, and various classroom dynamics make teachers often experience negative emotions, such as frustration and anger. The challenge becomes greater when teachers have an inclusive class. Emotional intelligence training is one of way to improve this social-emotional competence. This study aims to develop and test the validity of CARE module for primary school teachers, especially in inclusive schools. The content validity test will use Aiken’s V for the data analysis. The empirical test will be conducted by using quasi-experimental with untreated control group design with dependent pretest and posttest. Result shows that CARE module has good content validity with Aiken’s V 0.75-0.96, but emotional intelligence not significantly improved U (n=16) = 21, p >.05, in experiment group (M=12) than control group (M=1,9).